3D nonlinear finite element modelling of mechanical behavior of a new wall-beam-strut joint for prefabricated underground construction and validation again experimental testing. (October 2021) - Liu, Tingjin; Lu, Jiandong; Wang, Di; Liu, Hongyuan; Mo, Nuanjiao; Zhai, Lihua
Abstract: This paper studies the nonlinear mechanical performance of a new wall-beam-strut joint with the welded steel plate connection proposed for prefabricated underground construction under monotonic and low-reversed cyclic loading conditions using the three-dimensional finite element method with the concrete damaged plasticity model. The load-displacement curve, concrete cracking distribution, reinforcement strain, hysteresis loop curve, skeleton curve, and stiffness degradation obtained from the numerical modelling are compared with those from the full-scale experimental testing, which agree well with each other. However, the numerical modelling overestimates the yield load and ultimate bearing, underestimates the stiffness degradation and fail to capture the pinching effect compared with the experimental testing due to the limitation of the numerical modelling in simulating the slippage between the concrete and reinforcement after the concrete cracking. After that, the influence of the dilation angle, viscosity parameter and mesh sizes on the numerical modelling results was discussed. It is recommended that the range of the dilation angle should be between 25 degrees and 35 degrees and the viscosity parameter should be selected based on the parametric analyses. For optimization, with enough safety factor and good ductility, the longitudinal reinforcement ratio of the strut can be reduced to 1.16%. Finally, it is concluded that the wall-beam-strut joint with the welded steel plate connection has good mechanical performance under both monotonic and cyclic loading conditions, which provides a new joint connection method for the emerging prefabricated underground construction.